THE RESULTS OF SCREENING WITH SELDI-TOF-MS METHOD IN BREAST CANCER DIAGNOSIS - Can Atalay; Dilek Kubilay (European Journal of Breast Health, 2011)

(untitled)
Purpose:Diagnosis of breast cancer at an early stage with screening methods prolongs patients’ survival. The most commonly used screening method is mammography, however, this method is not sufficient, especially in younger women. For this reason, in this study, it is aimed to screen healthy individuals for breast cancer with recently developed SELDI-TOF-MS method.Patients and Methods:Protein profiles of healthy women screened between 2008 and 2009 were obtained from their serum samples using the SELDI-TOF-MS method. In serum samples, a decrease in BC1 protein level and an increase in BC2 and BC3 protein levels were identified as to carry a risk for breast cancer. Individuals carrying a risk were evaluated for possible breast pathologies.Results:Eighteen healthy women were included in the study. In four women (22.2%), peak value of BC1 protein was found as significantly low, whereas peak values of BC2 and BC3 proteins were significantly high. Cystic changes and complicated cysts were detected in one of the patients on ultrasonography.Conclusion:Although the number of individuals included in this study is small, women possesing a protein profile similar to breast cancer patients was detected. Following only these women who were identified will decrease labour force and expenses compared to following all women.